Kajian Kualitas Air Laut dan Sebaran Indeks Pencemaran di Pesisir Utara Kecamatan Palang-Tuban pada Musim Kemarau - Mukamto; Hidayah, Euis Nurul; Susilowati (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2024)
The northern coastal area of ​​Palang Sub-District is a densely populated area in the Tuban district with high differentiation of economic activities. The large population and heterogeneous community activities on the northern coastal of Palang Sub-District have the potential to become a source of pollution which results in a decrease in seawater quality. The research aim is to analyze seawater quality on the north coast of Palang Sub-District based on seawater quality parameters and the spatial distribution of the pollution index. It is hoped that this research can help local governments to monitor and control water pollution in the area. Sea water sampling was carried out in the dry season for 2 days at high and low tide conditions. This research analyzes the concentration values ​​of BOD, COD, NO3-, TSS, detergent, oil & grease, pH, temperature, and Total coliform compared to seawater quality standards of PP RI No. 22 of 2021 Appendix VIII on Marine Biota. The spatial distribution of the water quality pollution index is the result of interpolation using the Inverse Distance Weighted (IDW) method from the results of measuring test parameters. The Pearson Correlation statistical test was carried out to determine the level of correlation between the parameters selected in determining water quality. The results of the research show a decline in the quality of the northern coastal waters of Palang-Tuban District with several parameter concentration average values ​​exceeding the quality standards, namely pH = 6.9 (QS = 7.0-8.5); TSS = 29.2 ppm (QS= 20 ppm); Nitrate = 0.4 ppm (QS = 0.06 ppm), BOD5 = 54.8 ppm (QS= 20 ppm), COD = 112.5 ppm (QS= 100 ppm). The water quality status shows that the water conditions are moderately polluted (ST1A), lightly polluted (ST1B-ST5B), and good conditions (ST4C & ST5C). Controlling and reducing the pollution load entering coastal waters needs to be carried out to prevent the quality of coastal waters from decreasing further. One of them is by creating wastewater treatment at every fishing port and fish auction.